Proposta de aplicativo para subsidiar a aprendizagem da ortografia no ensino fundamental II - Souza, Cristiane Ferreira (2020)
The orthographic norm is one of the important components in the production of texts from the communicative process for a successful practice in interaction in society. Added to this the need to master the digital literacies, giving rise to success in the new paradigms of the fourth industrial revolution. Therefore, the school has a primary role in teaching the student to write correctly, using tools such as the digital educational game, providing the student with learning by playing. Thus, the present work aims to propose an orthographic application that aims to promote the improvement of the writing competence of Elementary School students, within the specific scope of the orthographic standard, having as a theoretical contribution the orthographic organization of our mother tongue (direct regularities, contextual regularities, morphological-grammatical regularities and irregularities), digital literacies and theory for the development of digital games with an emphasis on educational digital games. The relevance of such research is justified by the very recurrent presence of orthographic deviations among elementary school students, as well as the lack of pedagogical and financial resources at school, and the short time of the teacher to deal with these difficulties, in addition to the lack of more attractive teaching of spelling through digital information and communication technologies (DICTs), particularly the digital game. This last one lives up to the new era of cyberculture, where almost all students carry a mobile device and are connected via the internet, experiencing an intense virtual immersion. The methodology used is characterized by the indirect documentation and the description of the spelling process of the orthographic games for mobile devices (cell phones, tablets and notebooks) and desktop computer (desktop), resulting in a proposal for an orthographic, descriptive and reflective application, of educational digital games. The theoretical basis that guided the research was constituted, in the orthographic approach, according to: Morais (2010), Nóbrega (2013), Rocha et al. (1995) and Rojo (2009). The approach of digital literacies, game theory and digital educational game, was according to: Dudeney, Hockly and Pegrum (2016), Filatro and Cairo (2015), Boller and Kapp (2018), Paul Schuytema (2017 ), Prensky (2012), Novak (2017), Meira and Blikstein (2020). The application was called Spelling and consists of three games. The first game is about alphabetical the order of the alphabetical system, it is called Pindorama, the second, it is about the various sounds of X, called Feira de Mangalho and the last game deals with the contextual regularities of graphemes L and R, it is called Pastel com Caldo de Cana.